EFEK AKUNTANSI KONSENVARTISME TERHADAP KINERJA KEUANGAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERATING (Studi Pada Perusahaan sektor Basic Property dan Real Estatel di Burs Efek Indonesia) - Murdijanigsih, Tjahjani; Yubiharto, Yubiharto; Sudari, Sri; Priyatama, Tuggul (Medikonis, 2023)
ABSTRAC Accounting conservatism is a prudent reaction in dealing with the uncertainty inherent in the company to try to ensure that the risks and risks in the business environment have been considered. This study aims to examine whether accounting conservatism can affect financial performance and whether earnings management can strengthen the relationship between accounting conservatism and financial performance. The sample in this research is property and real estate companies listed on the Indonesia Stock Exchange from 2015 to 2019. The total sample is 30 companies according to the existing criteria with an observation period of 5 years, so a total of 150 observations. The results of this study are that accounting conservatism has a significant positive effect on financial performance. Meanwhile, earnings management cannot moderate (strengthen) the relationship between accounting conservatism and financial performance. This shows that in improving financial performance through accounting conservatism not by presenting earnings management but other company policies. Recomendation for further researchers are advised to replace moderating variables such as financial distress because it is suspected that companies that experience financial difficulties and do not experience financial difficulties will carry out different conservatism accounting. Keywords: Accounting Conservatism, Financial Performance and Earnings Management, ROA, Accrual and